What is Qualitative Research? - Hammersley, Martyn (Bloomsbury Academic, 2012)
This book provides an inviting introduction to qualitative research, one that is designed to stimulate reflection on its character and prospects. I‰What is Qualitative Research? /I‰offers clear definitions of key terms and concepts, as well as a thorough discussion of the various kinds of data used. Different types of qualitative investigation are examined, and key concepts and issues discussed. There will also be an examination of important debates within qualitative research about its proper character and future direction. This book examines the nature of qualitative research, the contrast with quantitative method, and the variety of forms that qualitative inquiry now takes. Comprehensive examination coupled with illustrative examples clarifies the differences and disagreements among qualitative researchers. Covering important topics such as research design, data production and analysis and the politics of representation, I‰What is Qualitative Research?/I‰ will be a vital resource for both new and experienced researchers.